March Madness in Wall Street : (What) Does the Market Learn from Stress Tests? - Fernandes, Marcelo (IMF Working Papers; Working Paper ;, 2015)
Annual stress tests have become a regular part of the supervisors' toolkit following the global financial crisis. We investigate their capital market implications in the United States by looking at price and trade reactions, information asymmetry and uncertainty indicators, and bank activities. The evidence we present supports the notion that there is important new information in stress tests, especially at times of financial distress. Moreover, public disclosure seems to help reduce informational asymmetries. Importantly, public disclosure of stress test results (and methodology) does not seem to have reduced private incentives to generate information or to have led to distorted incentives.